The relationship between monocyte to high-density lipoprotein cholesterol ratio and diabetic nephropathy - Onalan, Erhan (Professional Medical Publications, 2019)
Objective: This study aims to investigate the relationship of monocyte to high-density lipoprotein cholesterol ratio (MHR) with diabetes mellitus (DM) and diabetic nephropathy. Methods: This study included 262 Type-2 diabetes mellitus patients, of which 60 had diabetic nephropathy and 202 did not have diabetic nephropathy who presented to the internal diseases polyclinic at Firat University Medical Faculty Hospital between May 2018 and October 2018 and 50 healthy control subjects. A retrospective scan of patient files was conducted and information relevant to nephropathy such as hemoglobin, glycated hemoglobin levels (HbA1c), hematocrit count (HCT), monocyte count, LDL, HDL, triglyceride levels, and microvascular complications were acquired. Results: We determined MHR values as 11.9 +/- 5.5 and 8.4 +/- 2.9 respectively for the diabetic and healthy groups. There was a statistically significant difference between the two groups in terms of MHR, with a positive correlation between diabetes and MHR (< 0.001; r: 0.241). Moreover, glucose, HDL, and triglyceride levels were different between the two groups with statistical significance (respectively, p< 0.001; p< 0.001; p< 0.001). Our study found higher MHR levels for patients with diabetic nephropathy compared to those without diabetic nephropathy (respectively, 17.1 +/- 7.9 and 10.3 +/- 3.3) and determined statistical significance and a negative correlation (p< 0.001; r: -0.512). Conclusion: Our results suggest that an elevated MHR can be a biomarker for diabetic nephropathy, allowing the detection of diabetic nephropathy with simple and inexpensive laboratory tests.
Keywords: Diabetes Mellitus; Diabetic Nephropathy; Monocyte count to high-density lipoprotein cholesterol ratio